EFEKTIVITAS METODE SMALL GROUP DISCUSSION DALAM MENINGKATKAN PENGETAHUAN DAN SIKAP MAHASISWA KEBIDANAN - Saufa Yarah; Cut Rahmi Muharrina; Rawi Juwanda; Bilqis Laina Laina (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study attempts to know what it is small disscussion group, learning outcomes and effectiveness improve learning outcomes through this method sgd, the methodology that apply is literature review, using textbooks or mineral resources for its e-book and journals lab data required.As for the research used is small disscussion group, learning outcomes and improve learning outcomes through the method effectiveness sgd. Discussion of research is about small group disscussion sharing experiences and ideas is a technique that gives equal opportunity for every panulis to provide input and respond to the panel the masing-masing.Small group discussions is the method where students in the small group communicate directly with other members, share information and make an opinion to resolve problems relating